2017
DOI: 10.1002/ajh.24827
|View full text |Cite
|
Sign up to set email alerts
|

Missing HLA C group 1 ligand in patients with AML and MDS is associated with reduced risk of relapse and better survival after allogeneic stem cell transplantation with fludarabine and treosulfan reduced toxicity conditioning

Abstract: Reduced-toxicity conditioning with fludarabine and treosulfan is a dose-intensive regimen with enhanced anti-leukemia effect and acceptable toxicity in AML/MDS. HLA-C regulates natural-killer (NK) cell function by inhibiting Killer immunoglobulin-like receptors (KIR) and is divided into C1 and C2 epitopes. The missing-ligand theory suggests that missing recipient KIR ligands drives NK-alloreactivity after SCT, in the absence of HLA-mismatch by activating unlicensed donor NK cells. We analyzed SCT outcomes in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
(137 reference statements)
1
5
0
Order By: Relevance
“…Thereafter, Treo was approved by the European Medicines Agency (EMA) at a total dose of 30 g/ m 2 according to the results of a multicenter randomized phase 3 trial in older and comorbid patients. 15 Although potentially limited by the presence of single-center data, our long-term analysis confirms that a full-dose Treo-based conditioning regimen displays a strong myeloablative and immunosuppressive potential coupled with a good safety profile, in line with other recent studies (9,15,(20)(21)(22)(23)(27)(28)(29). A fast and stable full donor engraftment was achieved by most of our patients, toxicities were limited, and no case of SOS was reported.…”
Section: Discussionsupporting
confidence: 87%
“…Thereafter, Treo was approved by the European Medicines Agency (EMA) at a total dose of 30 g/ m 2 according to the results of a multicenter randomized phase 3 trial in older and comorbid patients. 15 Although potentially limited by the presence of single-center data, our long-term analysis confirms that a full-dose Treo-based conditioning regimen displays a strong myeloablative and immunosuppressive potential coupled with a good safety profile, in line with other recent studies (9,15,(20)(21)(22)(23)(27)(28)(29). A fast and stable full donor engraftment was achieved by most of our patients, toxicities were limited, and no case of SOS was reported.…”
Section: Discussionsupporting
confidence: 87%
“…In all, FT14 was associated with better outcomes in patients with active disease at SCT, but this conclusion must be taken with caution because of the retrospective nature of this study and heterogeneity of the patient groups. Several prior studies found no significant differences between the various treosulfan doses [11,18,19,21]. Most found similar NRM, whereas some showed higher relapse rates in the lower dose [11].…”
Section: Discussionmentioning
confidence: 91%
“…The combination of fludarabine and treosulfan (FT) has been introduced over the last few years [10][11][12][13][14][15][16][17][18][19][20][21]. It was reported mostly in patients with AML and MDS [10][11][12][13][14][15][16][17][18][19] but also in lymphoid malignancies [20], acute lymphoblastic leukemia, and in pediatric patients [21]. The Acute Leukemia Working Party (ALWP) of the European Society for Blood and Marrow Transplantation (EBMT) has recently reported the outcome of treosulfan-based conditioning in a relatively large group of 520 adult patients with AML [19].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, the evidence base is building to show that recipients who are homozygous for HLA C1 or C2 group alleles are disadvantaged in the HPCT setting compared with those who are heterozygous (Cook et al, 2004; Cooley et al., 2014; Neuchel et al., 2017; Shimoni et al., 2017; Sobecks et al., 2015). Moreover, the evidence highlighting worse outcomes for HLA C2/C2 group recipients (approximately 20% of the population) is reproducible for all donor categories (related, unrelated, haploidentical, UCB).…”
Section: Non‐hla Factors To Be Considered For Related and Unrelated Dmentioning
confidence: 99%